Convergent Approaches and Biological Activity of C1 and/or C3 Mono or Diamino Derivatives of 1α, 25‐Dihydroxy‐19‐nor‐vitamin D3. Key Enzymatic Desymmetrization of A‐Ring Synthon Precursor. Issue 2 (18th January 2023) - González‐García, Tania; Verstuyf, Annemieke; Verlinden, Lieve; Fernández, Susana; Ferrero, Miguel
Abstract: Three novel 19‐ nor ‐1α, 25‐dihydroxyvitamin D3 derivatives modified at C1 and/or C3 with an amino group were synthesized to study the influence of the substitution of one or both hydroxyl groups of A‐ring by amino groups on the affinity for vitamin D receptor (VDR) and vitamin D binding protein (hDBP), and also on the antiproliferative activity. The A‐ring precursors were prepared from cis, cis ‐1, 3, 5‐cyclohexanetriol applying a desymmetrization reaction of a prochiral 1, 3‐diol catalyzed by Pseudomonas cepacia lipase as a key step. The structural elucidation of diastereoisomers were unambiguously assigned by NMR spectroscopy. Abstract :